INTEGRASI NILAI NILAI PANCASILA MELALUI KEGIATAN KEAGAMAAN DALAM PROGRAM JAM KE NOL - Fitriya, Rosma (Graduate Program Magister Manajemen Pendidikan, 2017)
A zero hour program is initiated by Disdikpora and the Government of Palembang City. This program is an effort to develop morals through religious activities held 20 minutes before the instructional process takes place. This program can also be used as a forum for introducing and practicing the value of Pancasia through religious activities. The purpose of this study was to explain the implementation of the recognition and understanding of the value of Pancasila through zero hour activities in SMK PGRI 3 of Palembang. This research was a qualitative research. The research approach used was case study. The process of collecting and extracting the data involved observation methods, interviews, and documentation. Interactive analysis model was used in analyzing the data. The results of the research were: (1) Educational institution had an important role in the effort to foster the value of Pancasila and religion to the students, (2) Zero hour program could be a medium to integrate Pancasila value with religious values, (3) The implementation of the introduction and practice of the value of Pancasila through Zero hour program at SMK PGRI 3 Palembang includeed (a) the spirit of nationality, (b) upholding unity, and (c) justice, (4) the impacts and benefits of this program could be seen through some facts. First, the students not only did became religious but their behaviors also reflected the values of honesty, self-control, mutual respect, cooperation, responsibility, and discipline.